A new approach to bioanalysis: aqueous normal-phase chromatography with silica hydride stationary phases. (April 2012) - Pesek, Joseph J; Matyska, Maria T
Stationary phases based on silica hydride have demonstrated a number of unique properties that are especially advantageous for bioanalyses. They have excellent retention capabilities for hydrophilic compounds, which have been the most difficult to analyze by standard reversed-phase methods and, in many cases, can outperform newer approaches for the analysis of polar molecules, such as hydrophilic liquid interaction chromatography. In addition, all columns utilizing silica-hydride materials can be used in either the normal-phase or reversed-phase modes, sometimes retaining both polar and nonpolar compounds simultaneously. These stationary phases have a high degree of reproducibility and long-term stability.